Introduction: Urban-Rural Differences in Historical Demography - Christa Matthys; Jan Kok; Richard Paping (Historical Life Course Studies)
Systematic research on urban-rural variation in demographic behavior is necessary to overcome dichotomous views resulting from studying cities and the countryside separately. After all, a web of interactions facilitating the diffusion of ideas and behavior connects cities and rural areas. That is why it is especially important to study the comportment of migrants moving between urban and rural environments. In line with this argument five case studies are presented in this special issue that use static or dynamic individual-level data to analyze urban-rural demographic differences and life courses of migrants in Europe (Germany, the Netherlands and Scotland), mainly during the nineteenth century. The outcomes show that the places of residence indeed influenced demographic behavior to a considerable extent, although they do not reflect a simple and strict division between cities and rural areas. Rather, demographic behavior was affected by a diversity of local conditions, including various town sizes, calling for a further exploration of the impact of local demographic, working and living conditions. The studies in this issue also warn against simplified views regarding migrants in the past, for instance, their depiction of being of relatively humble social background. For many migrants, their migration was not a definitive break with the place of origin, and they did not assimilate completely to the dominant behavior in their destination. Instead, migrants often remained embedded in and influenced by trans-regional social networks.